Aspects of road and rail tunnels design and construction in mountainous areas - Patnaree Patipipat; Chao, Kuo Chieh; Noppadol Phien-Wej; Avirut Puttiwongrak; Pham, Huy Giao; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
The study has reviewed the design and construction aspects of road and rail tunnels and compared them to the road and rail tunnels projects in Thailand. The decisions about tunnel configuration and distance of emergency exits have to be made in the early stages of the design process. Moreover, the design of tunnel lining, waterproof system, and ventilation systems are crucial, and they have a marginal impact on road and rail tunnel safety and operation. As a result, the significant decision can be seen based on the long length of tunnels in mountainous areas. The evaluation and discussion of the case example aim to identify the probable geohazard affecting the design and construction of the representative tunnel projects in the vicinity of Tak {u2013} Mae Sot. The Tak {u2013} Mae Sot Road and Rail Tunnels lie in the western part of Thailand. The feasibility study of the projects was carried out, and the geological information and typical design were reviewed and discussed. According to the available geological data and literature reviews, a comprehensive study of the geological conditions of the proposed tunnels was carried out. The potential of geohazards was discussed and evaluated based on the geological characteristic of rock formations in relation to the influence of the tectonics setting of western Thailand. The limited investigation information results in a geological constraint model of the corridor and leads to high risks due to uncertainties. Therefore, subsurface investigation methods are recommended for the further state of the investigation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Geotechnical and Earth Resources Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2022
Keywords: Tunnels -- Design and construction -- Thailand